Adsorption Properties and Inhibition of C38 Steel Corrosion in Hydrochloric Solution by Some Indole Derivates: Temperature Effect, Activation Energies, and Thermodynamics of Adsorption. (4th June 2013) - Lebrini, M.; Robert, F.; Roos, C.
Abstract : The corrosion rates in the presence of some indole derivates, namely, 9H-pyrido[3, 4-b]indole (norharmane) and 1-methyl-9H-pyrido[3, 4-b]indole (harmane), as inhibitors of C38 steel corrosion inhibitor in 1 M HCl solution, were measured by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques, in the range of temperatures from 25 to 55 ∘ C. Results obtained revealed that the organic compounds investigated have inhibiting properties for all temperatures. The inhibition was assumed to occur via adsorption of the indole molecules on the metal surface. Adsorption of indole derivates was found to follow the Langmuir isotherm. The apparent activation energies, enthalpies, and entropies of the dissolution process and the free energies and enthalpies for the adsorption process were determined by potentiodynamic polarization and electrochemical impedance. The fundamental thermodynamic functions were used to collect important information about indole inhibitory behaviour.